DIAGNOSTICS OF THE LEVEL OF DEVELOPMENT OF CIVIC POSITION IN HIGH SCHOOL STUDENTS WITH DISABILITIES (Revista Inclusiones, 2020)
Objective: Diagnostics of the level of development of civic position in high school students with disabilities. Methods: The research relies on general scientific methods of cognition, such as analysis, synthesis, comparison, generalization, as well as pedagogical experiment (ascertaining) and analysis of empirical data. Results: The conducted research allows the authors to obtain qualitative and quantitative data on the level of development of civic position in high school students with disabilities. Conclusions: The obtained data prove the assumption about the necessity of targeted civic education of high school students with disabilities aimed not only at their enrichment with knowledge and skills in the sphere of civic studies but also at the development of steadfast civic position as an integrative personal quality, which is manifested in conducting civic activity. The article can be of interest to specialists and teachers of educational organizations who are concerned with the development of civic position in high school students with disabilities.